2011
DOI: 10.1002/wnan.143
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming in vivo barriers to targeted nanodelivery

Abstract: Nanoparticles have been investigated as promising nanocarriers for delivery of imaging and therapeutic agents for several decades, but have met with limited success. Although enormous progress in the fields of nanotechnology and nanoscience has been achieved, basic discoveries have not yet translated into effective targeted therapies. Nanoparticles can potentially improve the pharmacokinetics and pharmacodynamics of drugs; however, the complexity of in vivo systems imposes multiple barriers that severely inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
155
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(164 citation statements)
references
References 121 publications
0
155
0
1
Order By: Relevance
“…In the bloodstream, PLGA-NPs of this size can escape from clearances in the kidneys and reticuloendothelial system, which prolongs the blood retention time. This results in effective drug delivery to the target site with increased vascular permeability 42,43) . In addition, inflammatory cells, especially monocytes/macrophages, take up these sized particles, suggesting the potential of PLGA-NPs as a platform for novel anti-inflammatory therapies.…”
Section: Plga Nanoparticles For the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…In the bloodstream, PLGA-NPs of this size can escape from clearances in the kidneys and reticuloendothelial system, which prolongs the blood retention time. This results in effective drug delivery to the target site with increased vascular permeability 42,43) . In addition, inflammatory cells, especially monocytes/macrophages, take up these sized particles, suggesting the potential of PLGA-NPs as a platform for novel anti-inflammatory therapies.…”
Section: Plga Nanoparticles For the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…316,317 Some examples of imaging modalities include magnetic nanoparticles for cell labeling and observation by magnetic resonance imaging and quantum dots, carbon nanotubes, or radionuclides for in vivo observation of cells by positron-emission tomography (PET) or single-photonemission computed tomography. [318][319][320] Although PET provides great sensitivity, it lacks spatial resolution.…”
Section: From Single To Multiple Bioactive Factor Delivery For Skeletmentioning
confidence: 99%
“…3,4 Considerable research, particularly studies conducted in subcutaneous mouse tumor models, has demonstrated this effect over the last decade, but the magnitude of the extravascular delivery has depended on high intravascular overdosing of agents, prolonging particle systemic half-life (eg, pegylation), and decreasing particle size. 5 Unfortunately, clinical hope for the enhanced permeability and retention effect has waned with recognition that this mechanism is severely curtailed in nonsubcutaneous tumor mouse models, larger mammalian preclinical models, and humans.…”
Section: See Accompanying Article On Page 1178mentioning
confidence: 99%